2009
DOI: 10.1098/rsbl.2009.0204
|View full text |Cite
|
Sign up to set email alerts
|

Social structure of primate interaction networks facilitates the emergence of cooperation

Abstract: Animal cooperation has puzzled biologists for a long time as its existence seems to contravene the basic notion of evolutionary biology that natural selection favours 'selfish' genes that promote only their own well-being. Evolutionary game theory has shown that cooperators can prosper in populations of selfish individuals if they occur in clusters, interacting more frequently with each other than with the selfish. Here we show that social networks of primates possess the necessary social structure to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 19 publications
(23 reference statements)
2
50
0
Order By: Relevance
“…In particular for the latter, theoretical models show positive effects on cooperation levels (17)(18)(19)(20)(21). Congruent with this theoretical work, evolutionary simulations based on social networks of nonhuman primates show that, for example, these natural networks have the appropriate static structure to potentially support cooperation (8). By using social network analysis, we can now investigate not only the effects on the evolution of cooperative behavior, but also the existing social network properties and their effects on the individual's behavior (22).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…In particular for the latter, theoretical models show positive effects on cooperation levels (17)(18)(19)(20)(21). Congruent with this theoretical work, evolutionary simulations based on social networks of nonhuman primates show that, for example, these natural networks have the appropriate static structure to potentially support cooperation (8). By using social network analysis, we can now investigate not only the effects on the evolution of cooperative behavior, but also the existing social network properties and their effects on the individual's behavior (22).…”
mentioning
confidence: 90%
“…15). Homogenous networks are generally not found in nature; instead, natural social networks are usually heterogeneous networks (8,16). In particular for the latter, theoretical models show positive effects on cooperation levels (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the traditional well-mixed population, individuals interact only with some neighbors in a structured population. In such a heterogeneous environment, cooperators could survive by forming cooperative clusters to resist the invasion and exploitation of defectors [27,28]. The above network effect is called network reciprocity.…”
mentioning
confidence: 99%
“…This occurred even in the presence of ties that connected otherwise "socially distant" individuals, thereby allowing clusters of cooperators to be more easily invaded by defectors. Turning to real-life networks, simulations using 70 nonhuman primate social networks found that primate social structure often-though not always-facilitated cooperation (Voelkl & Kasper, 2009). …”
Section: Cooperationmentioning
confidence: 99%